The CENP-B homolog, Abp1, interacts with the initiation protein Cdc23 (MCM10) and is required for efficient DNA replication in fission yeast - Locovei, Alexandra M (BioMed Central, 2006)
Abp1, and the closely related Cbh1 and Cbh2 are homologous to the human centromere-binding protein CENP-B that has been implicated in the assembly of centromeric heterochromatin. Fission yeast cells lacking Abp1 show an increase in mini-chromosome instability suggesting that Abp1 is important for chromosome segregation and/or DNA synthesis. Here we show that Abp1 interacts with the DNA replication protein Cdc23 (MCM10) in a two-hybrid assay, and that the Δabp1 mutant displays a synthetic phenotype with a cdc23 temperature-sensitive mutant. Moreover, genetic interactions were also observed between abp1(+ )and four additional DNA replication initiation genes cdc18(+), cdc21(+), orc1(+), and orc2(+). Interestingly, we find that S phase is delayed in cells deleted for abp1(+ )when released from a G1 block. However, no delay is observed when cells are released from an early S phase arrest induced by hydroxyurea suggesting that Abp1 functions prior to, or coincident with, the initiation of DNA replication.